PREVALENCE OF EXTENDED SPECTRUM BETA LACTAMASE PRODUCING UROPATHOGENS IN PREGNANT WOMEN - THAPA, REKHA; LAMICHHANE, PRAMILA; BANJARA, MEGHA RAJ; ACHARYA, GANESH PRASAD (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: This study aims to determine the prevalence of urinary tract infection (UTI) among pregnant women and multidrug-resistant (MDR) uropathogens with reference to extended spectrum beta-lactamase (ESBL) producers. Methods: Three hundred urine specimens collected from pregnant women were studied. A semi-quantitative method was used for diagnosis of UTI. Isolation, identification, and antimicrobial susceptibility of an organism was done by standard microbiological procedure. ESBLs production was detected by double-disc synergy test method. Results: UTI was found among 30.5% of pregnant women. Among 137 Gram-negative bacterial isolates, 72.0% were found to be MDR while only 7.30% were ESBL producers. Among total of Escherichia coli and Klebsiella pneumoniae isolates, 7.69% and 15.38%, respectively, were found to be ESBL producers. Parity (odds ratio [OR]: 1.58, p<0.05), education status (OR: 4.07, p<0.01), occupation of pregnant women (OR: 1.86, p<0.05), times of bathing (OR: 3.45, p<0.01), history of UTI (OR: 20.79, p<0.01) were found to be significantly associated with UTI from both univariate and multivariate analysis. Gentamicin, nitrofurantoin, ceftazidime, and amikacin were found to be the most effective antibiotic against uropathogens. Conclusion: Frequent and consistent evaluation of the prevalence, etiologic agents, and predisposing factors of UTI during pregnancy is necessary in developing countries like Nepal in order to reduce its devastation effects during pregnancy on both maternal and fetal health. It is essential to have a regular and routine monitoring of ESBL producing clinical isolates in laboratory practice. Keywords: Pregnant women, Urinary tract infection, Multidrug resistance, Extended spectrum beta-lactamase.